Design and development an automatic plant pot prototype - Ismail I.N.B.; Iskandar A.H.B.; Eqwan M.R.; Zuhdi A.W.M.; Mohamad D.; Isa M.R.; Zahari N.M.; Zawawi M.H.; Mohamed H.; Ramli M.Z.; Mansor M.H. (American Institute of Physics Inc., 2023)
Gardening is an activity that requires fully care and time which two main factors of nowadays people lack of due to fast moving daily lifestyle. Growing a plant requires a person to monitor several parameters such as water, oxygen, nutrient, light, temperature and support for the plant. In conjunction to overcome the lack of commitment for the people to enjoy their hobby in gardening, an automatic plant pot is introduced. This paper discusses the studies of plant growth which later will be used as the criteria to design and develop a prototype of automatic plant pot. From the studies three outstanding elements were used as the main criteria to design a prototype of automatic plan pot which are water, nitrogen and temperature. These three elements need to be fully automated control to meet the objective that this prototype can help people to do gardening with less care and attention. 2018 Author(s).